Portrait of an Egyptian Shādhilī: Ibn Mughayzil (fl. 895/1490) and the Waking Vision of Prophet Muhammad - Polinsky, Sheridan (Journal of Sufi studies, 2025)
Research into the medieval Egyptian Shādhiliyya has centered around the founder, Abū l-Ḥasan al-Shādhilī (d. 656/1258), and the first major expositor, Ibn ʿAṭāʾ Allāh (d. 709/1309). This article aims to advance our knowledge of the order by exploring the life and thought of Ibn Mughayzil (fl. 895/1490), an erudite and skilled author who left behind a lengthy, wide-ranging work on Sufi thought. While the text reflects major themes of late Mamluk Sufism, it is distinguished primarily by its treatment of the waking vision of Prophet Muhammad. Responding to a debate in late ninth/fifteenth-century Cairo over the authenticity of this experience, Ibn Mughayzil gathers reports of waking visions and theoretical discussions to defend the vision as a rationally conceivable miracle. While his comprehensive engagement with the topic is itself original, he makes a critical intervention in the debate that buttresses Sufi claims to the vision in face of concerns about its feasibility and orthodoxy.